Diversity and distribution of smaU terrestrial rodents along a disturbance gradient in montane Costa Rica - Van den Bergh, M B (1998)
A total of 389 rodent captures in five unequally disturbed habitats in a Costa Rican montane cloud forest corresponded to 185 individuals (seven species, two faroilies). Species richness was similar for al l habitats, averaging 4-5 species/habitat. Population density and capture frequency were higher i n moderately disturbed habitats; Peromyscus mexicanus and Scotinomys xerampelinus were four to five times more cornmon than other murids. These species represented 79.4 % of all captures and 73.5 % of all captured individuals. Heteromyid species were rarely trapped. The importance of disturbance-mediated within-habitat microenvironmental heterogeneity fOI terrestrial small-sized rodent populations is stressed